Evaluasi Program R1N1 dalam Meningkatkan Derajat Kesehatan Masyarakat di Kota Surabaya - Rhohima, Nabila Naswa Zahra; Arida, Sagita Happy; Al Daufir, Daffa Mauludie; Angelina, Fellysita; Tauran; Sumarsyah, Wilda (FIA Unkris Press, 2026)
The R1N1 Program (One Neighborhood Unit, One Health Worker) is an innovation initiated by the Surabaya City Government to improve community access to health services through a community-based approach. However, the effectiveness of the program in achieving its intended objectives requires comprehensive evaluation. This study aims to evaluate the implementation of the R1N1 Program using the Context, Input, Process, Product (CIPP) evaluation model developed by Stufflebeam. A qualitative descriptive approach with a theoretical evaluation design was employed in Wonokromo District, Surabaya. Data were collected through in-depth interviews, field observations, and document analysis. Informants were selected using purposive sampling and included health workers, service users, and representatives from community health centers (Puskesmas). The findings indicate that the R1N1 Program is conceptually aligned with the principles of Primary Health Care (PHC), yet several implementation challenges remain. In the context dimension, the program lacks clear differentiation from existing community-based health services. In the input dimension, limited human resources and inadequate facilities contribute to increased workloads for health workers. The process dimension reveals inconsistencies in service schedules, which negatively affect community participation, particularly among productive-age groups. In the product dimension, the program has not demonstrated significant outcomes in reducing patient queues at community health centers or improving overall community health status. The study concludes that the effectiveness of the R1N1 Program can be enhanced through stronger program design, improved resource allocation, more adaptive service arrangements, and integrated health information management systems to ensure sustainable program performance.